High-density Sn < 2 + > doped silicon-boron-gadolinium scintillation glass as well as preparation method and application thereof

By using Gd2O3 and GdF3 in high-density scintillation glass to increase density and introducing Sn2+ as the luminescence center, a high-density, broadband luminescence efficiency and low-cost Sn2+ doped silicon boron gadolinium scintillation glass was prepared, which solved the problem of difficulty in taking into account both density and luminescence efficiency in the prior art, and realized the application of high-resolution X-ray imaging.

CN119638194AActive Publication Date: 2025-03-18HARBIN ENG UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411824898.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

While increasing the density of existing high-density scintillation glasses, it is difficult to ensure high scintillation efficiency, and are costly, and there are few researches on high-density scintillation glass materials in non-rare earth luminescent centers.

Method used

The density of the scintillation glass was improved by combining Gd2O3 and GdF3, and Sn2+ was introduced as a non-rare earth luminescence center, combined with SiO2, B2O3 and other oxides, and high-density Sn2+ doped silicon boron gadolinium scintillation glass with a density of 6-6.26 g/cm3 was prepared.

Benefits of technology

It realizes high-density, broadband luminescence efficiency and low-cost scintillation glass, with higher spatial resolution, and is suitable for high-resolution X-ray imaging and high-energy physics experiments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005183995850000081
    Figure BDA0005183995850000081
  • Figure BDA0005183995850000091
    Figure BDA0005183995850000091
  • Figure HDA0005183995860000011
    Figure HDA0005183995860000011
Patent Text Reader

Abstract

The invention discloses high-density Sn < 2 + >-doped silicon-boron-gadolinium scintillation glass as well as a preparation method and application thereof, and belongs to the field of scintillation luminescent materials. The high-density Sn < 2 + > doped silicon-boron-gadolinium scintillation glass comprises a main body component, a reducing agent and externally doped Sn < 2 + >, the main body components comprise SiO2, B2O3, Gd2O3, GdF3 and X, and the X is one or more of Al2O3, AlF3, BaO and BaF2; the molar percentages of SiO2, B2O3, Gd2O3, GdF3 and X are as follows: the molar percentage of SiO2 is 5 to 10 mol percent, the molar percentage of B2O3 is 15 to 30 mol percent, the molar percentage of Gd2O3 is 25 to 35 mol percent, the molar percentage of GdF3 is 25 to 35 mol percent, and the molar percentage of X is 5 to 15 mol percent; the sum of the main components is 100 mol%; the molar percentage of the reducing agent is 0.5-2 mol%; the molar percentage of the externally doped Sn < 2 + > is 0.5-2 mol%; the density of the high-density Sn < 2 + > doped silicon-boron-gadolinium scintillation glass is 6-6.26 g / cm < 3 >, the photoluminescence quantum efficiency is 75%-90%, the density, the photoluminescence quantum efficiency and the X-ray imaging resolution of the scintillation glass are greatly improved, and the preparation cost of the high-density scintillation glass is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of scintillation luminescent materials, and particularly relates to a high-density Sn 2+ Gadolinium-doped borosilicate scintillating glass, preparation method and application thereof. Background Art

[0002] With the rapid development of human beings in the fields of high-energy physics, nuclear physics, industrial non-destructive testing, medical imaging and safety testing, the performance requirements for scintillation materials are becoming more and more stringent.

[0003] Scintillating material is an energy conversion material that can convert high-energy rays such as X-rays and gamma rays or high-energy particle radiation into ultraviolet or visible light. Compared with traditional scintillating crystals, scintillating glass has the advantages of short preparation cycle, easy adjustment of composition, good sample uniformity, strong transparency, easy processing, mass production and fiber opticization.

[0004] Among them, in addition to the advantages of ordinary scintillating glass, the high material density of high-density scintillating glass can effectively deposit the energy of high-energy rays or particles within a limited distance, avoiding direct damage to electronic devices by high-energy rays or particles, and is expected to replace the expensive scintillating crystals in high-energy physics experimental equipment. However, due to the inherent defects inside the glass, it is difficult to ensure a high scintillation luminescence efficiency while increasing the material density, and most of the existing high-density scintillating glasses use rare earth ions as the luminescence center, and there are few studies on high-density scintillating glass materials with non-rare earth ions as the luminescence center. Here, the present invention provides a Sn 2+ luminescence center with non-rare earth ions as the luminescence center. 2+ High-density doped scintillating materials are used for high-resolution X-ray imaging.

[0005] At present, the density of most scintillating glass is 4.0g / cm 3 The following are limited applications in X-ray imaging fields such as non-destructive testing of industrial equipment and medical diagnosis. In order to increase the density of glass scintillators, a common method is to add oxide components of high atomic number elements. These components are beneficial to enhancing the efficiency of glass in depositing high-energy rays. The high-density scintillating glass currently under research mainly includes silicate glass, germanate glass, phosphate glass, etc. Most of the glass components with higher density contain heavy metal oxides such as TeO2, GeO2, and Lu2O3. The patent publication number is CN 107759079 B. By adding Lu2O3 raw materials to the glass, the glass density is increased to 6g / cm 3 , and enhances the radiation resistance of glass; the patent publication number is CN 114409252 A. By introducing high content of GeO2 and Lu2O3 into the glass matrix, the glass density can reach 6.046g / cm 3Patent publication number CN 110451795B, by adding high content of TeO2, Lu2O3 and WO3 into the glass matrix, the glass density can be increased to 6.5g / cm 3 . However, the raw materials of GeO2 and Lu2O3 are relatively expensive, which greatly increases the manufacturing cost of scintillating glass. Lu2O3 also introduces radiation background, which reduces the energy resolution of scintillating glass. Therefore, the development of scintillating glass with high density, high brightness (light yield), low cost and high resolution is still a hot spot and difficulty in the current scintillating glass field. In addition, glass scintillators with rare earth luminescence centers have been widely studied, while glass scintillators without rare earth luminescence centers have rarely been reported. Summary of the invention

[0006] In view of the technical problems existing in the prior art, the present invention provides a high-density Sn 2+ The gadolinium-doped silicon boron scintillating glass and its preparation method and application can significantly increase the density of the scintillating glass by combining Gd2O3 and GdF3, while reducing the preparation cost of high-density scintillating glass, and can better meet the requirements of high-resolution X-ray imaging detection and high-energy physics experiments. 2+ Doped Si-Bo-Gd scintillating glass is a broadband luminescent glass scintillating material with a density of 6-6.26 g / cm 3 , photoluminescence quantum efficiency 75%-90%. The X-ray imaging unit prepared based on this achieved a higher spatial resolution (14-20lp / mm) than the commercial Csl:TI crystal (10-11lp / mm), proving that high-density Sn 2+ Potential application value of gadolinium-doped borosilicate scintillating glass in the field of X-ray imaging.

[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:

[0008] A high-density Sn 2+ Doped silicon boron gadolinium scintillating glass, including main component, reducing agent and externally doped Sn 2 + ;

[0009] The main components include SiO2, B2O3, Gd2O3, GdF3 and X, X is one or more of Al2O3, AlF3, BaO, BaF2; the molar percentages of SiO2, B2O3, Gd2O3, GdF3 and X are 5-10 mol% for SiO2, 15-30 mol% for B2O3, 25-35 mol% for Gd2O3, 25-35 mol% for GdF3 and 5-15 mol% for X respectively; the sum of the main components is 100 mol%;

[0010] The molar percentage of the reducing agent is 0.5-2 mol%;

[0011] The Sn-doped 2+ The molar percentage is 0.5-2 mol%.

[0012] The high density Sn 2+ The glass density of the gadolinium-doped borosilicate scintillating glass is greater than or equal to 6g / cm 3 , more specifically 6 to 6.26 g / cm 3 .

[0013] The high density Sn 2+ The photoluminescence quantum efficiency of the gadolinium-doped borosilicate scintillating glass is greater than or equal to 75%, more specifically 75%-90%.

[0014] The high density Sn 2+ When the silicon boron gadolinium-doped scintillation glass is excited by X-rays, its luminescence peak integrated intensity can reach 30%-80% of that of the BGO scintillation crystal.

[0015] Preferably, the reducing agent is one or more of Si3N4, AlN, SiC, and C.

[0016] Preferably, the externally doped Sn 2+ Introduced by SnO2 and / or SnO.

[0017] The present invention also provides a high-density Sn 2+ The preparation method of the gadolinium-doped borosilicate scintillating glass comprises the following steps:

[0018] S1: According to high density Sn 2+ The raw material components of the gadolinium-doped borosilicate scintillating glass are weighed, and the raw materials are fully ground and mixed to obtain a glass raw material mixture;

[0019] S2: melting the glass raw material mixture to obtain a uniform glass melt;

[0020] S3: Pour the uniform glass melt into the preheated mold, cool it into shape, and then transfer it to the annealing furnace for constant temperature annealing to eliminate internal stress and obtain high-density Sn 2+ Gadolinium-doped borosilicate scintillating glass.

[0021] In the above S1, whether to use the reducing agent as one of the glass raw material mixture is determined according to the type of reducing agent. When the reducing agent includes Si3N4 or AlN, it is ground and mixed evenly with other raw materials. When the reducing agent includes SiC or C, it is added before the melting process.

[0022] In the above-mentioned S2, a corundum crucible or a SiC crucible is used as a melting container, and a cover is added for melting.

[0023] Preferably, in step S2, when a corundum crucible is used, the melting temperature is 1250-1450°C, the melting time is 60-120 min, and the melting atmosphere is an air atmosphere; when a SiC crucible is used, the melting temperature is 1250-1350°C, the melting time is 60-120 min, and the melting atmosphere is an air atmosphere.

[0024] Preferably, in step S3, the preheating temperature of the mold is 400-600°C.

[0025] Preferably, in step S3, the annealing temperature is 400-600° C., and the annealing time is 3-8 hours.

[0026] Preferably, in step S3, after the annealing, the process further includes: a cooling process, including cooling the temperature to 150-200°C at a cooling rate of 5-10°C / min, and then cooling to room temperature in the furnace.

[0027] The present invention also provides a high-density Sn 2+ Application of Gadolinium-doped Si-Bo Scintillating Glass, the high density Sn 2+ Doped silicon boron gadolinium scintillating glass or high-density Sn prepared by the preparation method 2+ Gadolinium-doped borosilicate scintillating glass is used in X-ray medical imaging, radiation detection, and industrial non-destructive testing.

[0028] The high density Sn 2+ The application of gadolinium-doped borosilicate scintillating glass as an X-ray medical imaging unit with a spatial resolution of 14-20 lp / mm.

[0029] Compared with the prior art, the high-density Sn 2+ The borosilicate gadolinium-doped scintillating glass and its preparation method and application have the following beneficial effects:

[0030] The present invention adopts high density Sn 2+ The simultaneous use of Gd2O3 and GdF3 in the doped borosilicate gadolinium scintillating glass, combined with a molar ratio of Gd2O3:GdF3 of (1-5):(1-7), significantly increases the glass density to more than 6 g / cm 3 , high density Sn 2+ The total content of rare earth element compounds in the doped silicon boron gadolinium scintillating glass component can be as high as 55 mol%, and the mass fraction can reach 65%. 2+ The doped silicon boron gadolinium scintillating glass does not use traditional rare earth ions as the luminescence center, but uses Sn with broadband luminescence characteristics. 2+ As a luminescence center, different from the strong emission of traditional rare earth luminescence centers, Sn 2+ Ions as ns2 The type emission center is more suitable for broadband blue and white light emission. The visible light generated can also match the detection wavelength of equipment such as photomultiplier tubes or SIPM well, thereby realizing the effective detection of high-energy particles or rays.

[0031] The high-density Sn 2+ The doped silicon boron gadolinium scintillating glass has a high photoluminescence quantum efficiency, which can reach more than 75%. This is because the boric acid component is added, and the content of the component is 20-25mol%. Too high will cause the density of the glass to drop more, and too low will be unfavorable for glass melting. And it has a high light yield under X-ray excitation, and its luminescence peak integrated intensity can reach 30%-80% of BGO scintillating crystal. The reason is that it has better reduction of Sn and stronger luminescence.

[0032] The X-ray imaging unit prepared based on the scintillator involved in the present invention achieves a higher spatial resolution (14-20lp / mm) because the glass has good transmittance and is uniform inside without bubbles, so the X-ray imaging resolution is higher.

[0033] The high density Sn 2+ Doped Si-BG scintillating glass, the added GdF3 as heavy metal fluoride can not only provide Gd 3+ , and can also combine with Gd2O3, and control the added molar percentage to increase the density of the scintillating material, and reduce the melting temperature of the glass, reduce the viscosity, and at the same time improve the openness of the glass network structure and the solubility of rare earth oxides in the glass, and can further reduce the manufacturing cost of the glass. The addition of Gd2O3 can also ensure that the glass does not become devitrified due to excessive fluoride, and can also stabilize the transition temperature and crystallization starting temperature of the glass. The introduction of B2O3 can effectively reduce the preparation temperature of scintillating glass, thereby reducing the difficulty of manufacturing scintillating glass. As one of the X components, the introduction of Al2O3 / AlF3 can change the physical and chemical properties of the glass, enhance the mechanical strength and durability of the glass, and increase the transparency of the glass and its stability during heat treatment / cold treatment. The introduction of reducing agents such as Si3N4 can effectively provide a reducing atmosphere during the melting process of the glass, which can ensure that Sn 2+ Will not be oxidized.

[0034] The high density Sn 2+ Doped silicon boron gadolinium scintillating glass does not use compounds of heavy metal elements such as W, Pb, Lu, Ge, La, and Tl, and can have many advantages. For example, it does not contain Pb elements, which is friendly to the human body and the environment; it does not contain high-priced raw materials such as GeO2 and Lu2O3, so the preparation cost is lower and no radiation background is introduced; it does not contain raw materials with variable valence characteristics such as TeO2, Bi2O3, and WO3, and will not cause glass coloring during the glass melting process.

[0035] The scintillator glass involved in the present invention is easy to prepare in large size and can be prepared into large optical devices. 2+ High-density doped gadolinium-doped borosilicate scintillating glass has excellent chemical and physical stability. 2+ Doped scintillating glass is of great significance for promoting high-energy ray detection and realizing high-resolution X-ray imaging and other practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The high-density Sn of Example 1 2+ Comparison of X-ray excitation emission spectra of gadolinium-doped borosilicate scintillating glass and BGO crystal.

[0037] Figure 2 The high-density Sn of Example 2 2+ Comparison of X-ray excitation emission spectra of gadolinium-doped borosilicate scintillating glass and BGO crystal.

[0038] Figure 3 The high-density Sn of Example 3 2+ Comparison of X-ray excitation emission spectra of gadolinium-doped borosilicate scintillating glass and BGO crystal.

[0039] Figure 4 The high-density Sn of Example 4 2+ Comparison of X-ray excitation emission spectra of gadolinium-doped borosilicate scintillating glass and BGO crystal.

[0040] Figure 5 The high-density Sn of Example 5 2+ Comparison of X-ray excitation emission spectra of gadolinium-doped borosilicate scintillating glass and BGO crystal.

[0041] Figure 6 The high density Sn of Example 6 2+ Comparison of X-ray excitation emission spectra of gadolinium-doped borosilicate scintillating glass and BGO crystal.

[0042] Figure 7 The high density Sn of Example 7 2+ Comparison of X-ray excitation emission spectra of gadolinium-doped borosilicate scintillating glass and BGO crystal.

[0043] Figure 8 The high-density Sn of Examples 1, 2, and 3 2+ Morphology image of gadolinium-doped borosilicate scintillating glass.

[0044] Fig. 9 This is a logarithmic graph of the X-ray imaging resolution of Example 5. DETAILED DESCRIPTION

[0045] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The described embodiments are only partial examples of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] A high density Sn 2+ The invention discloses a gadolinium-doped borosilicate scintillation glass and a preparation method thereof, comprising the following steps:

[0048] High density Sn 2+ The components of the gadolinium-doped borosilicate scintillating glass and the molar percentages of the corresponding components are: 5SiO2-25B2O3-25Gd2O3-35GdF3-10AlF3-1.8SnO2; and also include 2 mol% of C.

[0049] 1. According to the above high density Sn 2+ The raw materials of the borosilicate gadolinium-doped scintillating glass component except the reducing agent are weighed and fully ground and mixed to obtain a glass raw material mixture;

[0050] 2. Pour the uniformly mixed glass raw material mixture into a covered corundum crucible, add a reducing agent with a molar percentage of 0.5%, that is, 5g of carbon powder as a reducing agent to provide a reducing atmosphere at the bottom of the corundum crucible, and melt it into a uniform glass melt in an air atmosphere at a melting temperature of 1300°C and a melting time of 60min;

[0051] 3. Pour the uniform glass melt into a mold preheated at 450℃ and cool it to form. Then transfer it to a 450℃ annealing furnace for constant temperature annealing to eliminate internal stress. After annealing for 6 hours, reduce the temperature to 150℃ at a rate of 6℃ / min, and then cool it to room temperature with the furnace to obtain high-density Sn 2+ Gadolinium-doped borosilicate scintillating glass.

[0052] Example 2

[0053] A high density Sn 2+ The invention discloses a gadolinium-doped borosilicate scintillation glass and a preparation method thereof, comprising the following steps:

[0054] High density Sn 2+ The components of the gadolinium-doped borosilicate scintillating glass and the molar percentages of the corresponding components are: 5SiO2-25B2O3-25Gd2O3-35GdF3-10Al2O3-1.8SnO2;

[0055] 1. According to the above high density Sn 2+The raw materials of the borosilicate gadolinium-doped scintillating glass component are weighed and fully ground and mixed to obtain a glass raw material mixture;

[0056] 2. Pour the uniformly mixed glass raw material mixture into a covered SiC crucible and melt it into a uniform glass melt in an air atmosphere at a melting temperature of 1300°C and a melting time of 80 minutes;

[0057] 3. Pour the uniform glass melt into a mold preheated at 500℃ and cool it to shape, then transfer it to a 500℃ annealing furnace for constant temperature annealing to eliminate internal stress. After annealing for 6 hours, reduce the temperature to 150℃ at a rate of 6℃ / min, and then cool it to room temperature with the furnace to obtain high-density Sn 2+ Gadolinium-doped borosilicate scintillating glass.

[0058] Example 3

[0059] A high density Sn 2+ The invention discloses a gadolinium-doped borosilicate scintillation glass and a preparation method thereof, comprising the following steps:

[0060] High density Sn 2+ The components of the gadolinium-doped borosilicate scintillating glass and the molar percentages of the corresponding components are: 5SiO2-25B2O3-25Gd2O3-35GdF3-10AlF3-1.8SnO; and also include 2 mol% of C.

[0061] 1. According to the above high density Sn 2+ The raw materials of the borosilicate gadolinium-doped scintillating glass component except the reducing agent are weighed and fully ground and mixed to obtain a glass raw material mixture;

[0062] 2. Pour the uniformly mixed glass raw material mixture into a covered corundum crucible, add 5g of carbon powder to the bottom of the crucible, and melt it into a uniform glass melt in an air atmosphere at a melting temperature of 1300°C and a melting time of 60min;

[0063] 3. Pour the glass melt into a mold preheated at 480℃ and cool it to shape, then transfer it to a 480℃ annealing furnace for constant temperature annealing to eliminate internal stress. After annealing for 6 hours, reduce the temperature to 150℃ at a rate of 6℃ / min, and then cool it to room temperature with the furnace to obtain high-density Sn 2+ Gadolinium-doped borosilicate scintillating glass.

[0064] Example 4

[0065] A high density Sn 2+ The invention discloses a gadolinium-doped borosilicate scintillation glass and a preparation method thereof, comprising the following steps:

[0066] High density Sn 2+The components of the gadolinium-doped borosilicate scintillating glass and the molar percentages of the corresponding components are: 5SiO2-25B2O3-25Gd2O3-35GdF3-5Al2O3-5BaO-0.5SnO2-1Si3N4;

[0067] 1. According to the above high density Sn 2+ The raw materials of the borosilicate gadolinium-doped scintillating glass component are weighed and fully ground and mixed to obtain a glass raw material mixture;

[0068] 2. Pour the uniformly mixed glass raw material mixture into a covered corundum crucible and melt it into a uniform glass melt in an air atmosphere at a melting temperature of 1350°C and a melting time of 90 minutes;

[0069] 3. Pour the uniform glass melt into a mold preheated at 550℃ and cool it to form. Then transfer it to a 550℃ annealing furnace for constant temperature annealing to eliminate internal stress. After annealing for 6 hours, reduce the temperature to 150℃ at a rate of 6℃ / min, and then cool it to room temperature with the furnace to obtain high-density Sn 2+ Gadolinium-doped borosilicate scintillating glass.

[0070] Example 5

[0071] A high density Sn 2+ The invention discloses a gadolinium-doped borosilicate scintillation glass and a preparation method thereof, comprising the following steps:

[0072] High density Sn 2+ The components of the gadolinium-doped borosilicate scintillating glass and the molar percentages of the corresponding components are: 10SiO2-20B2O3-25Gd2O3-35GdF3-5Al2O3-5BaF2-1SnO2-1Si3N4;

[0073] 1. According to the above high density Sn 2+ The raw materials of the borosilicate gadolinium-doped scintillating glass component are weighed and fully ground and mixed to obtain a glass raw material mixture;

[0074] 2. Pour the uniformly mixed glass raw material mixture into a covered corundum crucible and melt it into a uniform glass melt in an air atmosphere at a melting temperature of 1350°C and a melting time of 120 minutes;

[0075] 3. Pour the glass melt into a mold preheated at 550℃ and cool it to shape. Then transfer it to a 550℃ annealing furnace for constant temperature annealing to eliminate internal stress. After annealing for 6 hours, reduce the temperature to 150℃ at a rate of 6℃ / min, and then cool it to room temperature with the furnace to obtain high-density Sn 2+ Gadolinium-doped borosilicate scintillating glass.

[0076] Example 6

[0077] A high density Sn 2+ The invention discloses a gadolinium-doped borosilicate scintillation glass and a preparation method thereof, comprising the following steps:

[0078] High density Sn 2+ The components of the gadolinium-doped borosilicate scintillating glass and the molar percentages of the corresponding components are: 10SiO2-20B2O3-30Gd2O3-30GdF3-5Al2O3-5BaO-1.5SnO2-1Si3N4;

[0079] 1. According to the above high density Sn 2+ The raw materials of the borosilicate gadolinium-doped scintillating glass component are weighed and fully ground and mixed to obtain a glass raw material mixture;

[0080] 2. Pour the uniformly mixed glass raw material mixture into a covered SiC crucible and melt it into a uniform glass melt in an air atmosphere at a melting temperature of 1350°C and a melting time of 120 minutes;

[0081] 3. Pour the glass melt into a mold preheated at 550℃ and cool it to shape. Then transfer it to a 550℃ annealing furnace for constant temperature annealing to eliminate internal stress. After annealing for 6 hours, reduce the temperature to 150℃ at a rate of 6℃ / min, and then cool it to room temperature with the furnace to obtain high-density Sn 2+ Gadolinium-doped borosilicate scintillating glass.

[0082] Example 7

[0083] A high density Sn 2+ The invention discloses a gadolinium-doped borosilicate scintillation glass and a preparation method thereof, comprising the following steps:

[0084] High density Sn 2+ The components of the gadolinium-doped borosilicate scintillating glass and the molar percentages of the corresponding components are: 7SiO2-23B2O3-30Gd2O3-30GdF3-5Al2O3-5BaF2-1.8SnO2-1Si3N4;

[0085] 1. According to the above high density Sn 2+ The raw materials of the borosilicate gadolinium-doped scintillating glass component are weighed and fully ground and mixed to obtain a glass raw material mixture;

[0086] 2. Pour the uniformly mixed glass raw material mixture into a covered corundum crucible and melt it into a uniform glass melt in an air atmosphere at a melting temperature of 1350°C and a melting time of 120 minutes;

[0087] 3. Pour the glass melt into a mold preheated at 550℃ and cool it to shape. Then transfer it to a 550℃ annealing furnace for constant temperature annealing to eliminate internal stress. After annealing for 6 hours, reduce the temperature to 150℃ at a rate of 6℃ / min, and then cool it to room temperature with the furnace to obtain high-density Sn 2+ Gadolinium-doped borosilicate scintillating glass.

[0088] Comparative Example 1

[0089] The same as Example 2, except that the raw material components of the scintillating glass and the molar percentages of the components are: 5SiO2-25B2O3-60Gd2O3-10Al2O3-1.8SnO2. Since GdF3 is not added, the glass liquid becomes turbid and the compound is not completely melted, so that the glass transmittance deteriorates, affecting the performance test of the glass and reducing the photoluminescence quantum efficiency.

[0090] Comparative Example 2

[0091] The same as Example 4, except that the raw material components of the scintillating glass and the molar percentages of the components are: 5SiO2-25B2O3-60GdF3-5Al2O3-5BaO-0.5SnO2-1Si3N4. Since Gd2O3 is not added, the glass will have too much fluoride, and a large amount of fluoride will volatilize during the firing process, resulting in crystallization, thereby reducing the density, reducing the photoluminescence quantum efficiency, and reducing the integrated intensity of the luminescence peak.

[0092] Comparative Example 3

[0093] The same as Example 4, except that the raw material components of the scintillating glass and the molar percentage of each component are: 5SiO2-25B2O3-35Gd2O3-25GdF3-5Al2O3-5BaO-0.5SnO2-1Si3N4. Since the molar ratio of Gd2O3:GdF3 is 7:5, the oxide content increases, the melting point of the glass increases, and the problem of infusible materials occurs, thereby reducing the density, reducing the photoluminescence quantum efficiency, and reducing the integrated intensity of the luminescence peak.

[0094] Comparative Example 4

[0095] The same as Example 4, except that the raw material components of the scintillating glass and the molar percentage of each component are: 5SiO2-25B2O3-5Gd2O3-55GdF3-5Al2O3-5BaO-0.5SnO2-1Si3N4, because the Gd2O3 content is reduced and the GdF3 content is increased, a large amount of glass fluoride will volatilize during the melting and casting process, and crystallization will occur on the surface of the glass, thereby reducing the density, reducing the photoluminescence quantum efficiency, and reducing the integrated intensity of the luminescence peak.

[0096] Comparative Example 5

[0097] The same as Example 4, except that the raw material components of the scintillation glass and the molar percentage of each component are: 5SiO2-10B2O3-25Gd2O3-35GdF3-15Al2O3-10BaO-0.5SnO2-1Si3N4, the content of B in the scintillation glass becomes lower, and boric acid plays a fluxing role in the glass. A large reduction in boric acid will cause the glass to be completely infusible or devitrified into a ceramic state.

[0098] All high density Sn 2+ The density of the doped borosilicate glass is measured by Archimedes' principle using alcohol as the immersion liquid and a precision balance. 2+ The X-ray excited luminescence (XEL) spectra of Gd-SiB-doped scintillating glasses were measured by a Zolix Omni-λ300i spectrometer in reflection mode. Figure 1-7 The high-density Sn prepared in Example 1-7 2+ Comparison of X-ray excitation emission spectra of gadolinium-doped borosilicate scintillating glass and BGO crystal. Figure 8 These are pictures of the scintillation glass morphology of Examples 1, 2, and 3. Fig. 9 The X-ray imaging line logarithm resolution diagram of Example 5. The composition and density of the high-density borosilicate gadolinium scintillating glass of Examples 1-7 are shown in Table 1. 2+ Gallium boron gadolinium-doped scintillating glass has high density, high X-ray imaging resolution line pairs, and low cost. Therefore, it is suitable for medical imaging, radiation detection, industrial non-destructive testing and other fields.

[0099] Table 1 Density and performance comparison of scintillating glass prepared in Examples and Comparative Examples

[0100]

[0101]

Claims

1. A high-density Sn 2+ The gadolinium-doped borosilicate scintillating glass is characterized by: Including main components, reducing agent and external Sn doping 2 + ; The main components include SiO2, B2O3, Gd2O3, GdF3 and X, X is one or more of Al2O3, AlF3, BaO, BaF2; the molar percentages of SiO2, B2O3, Gd2O3, GdF3 and X are 5-10 mol% for SiO2, 15-30 mol% for B2O3, 25-35 mol% for Gd2O3, 25-35 mol% for GdF3 and 5-15 mol% for X respectively; the sum of the main components is 100 mol%; The molar percentage of the reducing agent is 0.5-2 mol%; The Sn-doped 2+ The molar percentage is 0.5-2 mol%.

2. The high-density Sn according to claim 1 2+ The gadolinium-doped borosilicate scintillating glass is characterized by: The high density Sn 2+ The glass density of the gadolinium-doped borosilicate scintillating glass is greater than or equal to 6g / cm 3 ; The high density Sn 2+ The photoluminescence quantum efficiency of the gadolinium-doped borosilicate scintillating glass is greater than or equal to 75%.

3. The high-density Sn according to claim 1 2+ The gadolinium-doped borosilicate scintillating glass is characterized by: The high density Sn 2+ When the silicon boron gadolinium-doped scintillation glass is excited by X-rays, its luminescence peak integrated intensity can reach 30%-80% of that of the BGO scintillation crystal.

4. The high-density Sn according to claim 1 2+ The gadolinium-doped borosilicate scintillating glass is characterized by: The reducing agent is one or more of Si3N4, AlN, SiC, C; and / or the externally doped Sn 2+ Introduced by SnO2 and / or SnO.

5. The high-density Sn according to any one of claims 1 to 4 2+ The method for preparing the gadolinium-doped borosilicate scintillating glass is characterized in that: The following steps are involved: S1: According to high density Sn 2+ The raw material components of the gadolinium-doped borosilicate scintillating glass are weighed, and the raw materials are fully ground and mixed to obtain a glass raw material mixture; S2: melting the glass raw material mixture to obtain a uniform glass melt; S3: Pour the uniform glass melt into the preheated mold, cool it into shape, and then transfer it to the annealing furnace for constant temperature annealing to eliminate internal stress and obtain high-density Sn 2+ Gadolinium-doped borosilicate scintillating glass.

6. The high-density Sn according to claim 5 2+ The method for preparing the gadolinium-doped borosilicate scintillating glass is characterized in that: In the S2, when a corundum crucible is used, the melting temperature is 1250-1450°C, the melting time is 60-120min, and the melting atmosphere is an air atmosphere; when a SiC crucible is used, the melting temperature is 1250-1350°C, the melting time is 60-120min, and the melting atmosphere is an air atmosphere.

7. The high-density Sn according to claim 5 2+ The method for preparing the gadolinium-doped borosilicate scintillating glass is characterized in that: In step S3, the preheating temperature of the mold is 400-600°C.

8. The high-density Sn according to claim 5 2+ The method for preparing the gadolinium-doped borosilicate scintillating glass is characterized in that: In step S3, the annealing temperature is 400-600° C. and the annealing time is 3-8 hours; And / or, after the annealing, the process further includes: a cooling process, including cooling the temperature to 150-200° C. at a cooling rate of 5-10° C. / min, and then cooling the temperature to room temperature in the furnace.

9. A high density Sn 2+ Application of doped borosilicate gadolinium scintillating glass, the high-density Sn as claimed in any one of claims 1 to 4 2+ Doped silicon boron gadolinium scintillating glass or high-density Sn prepared by the preparation method according to any one of claims 4 to 8 2 + Gadolinium-doped borosilicate scintillating glass is used in X-ray medical imaging, radiation detection, and industrial non-destructive testing.

10. The high-density Sn according to claim 9 2+ Application of gadolinium-doped borosilicate scintillating glass, characterized in that: The high density Sn 2+ The application of gadolinium-doped borosilicate scintillating glass is used in X-ray medical imaging, and the spatial resolution of the X-ray imaging unit is 14-20lp / mm.

Citation Information

Patent Citations

  • A Eu 3+ High-density scintillation glass doped with tellurate and its preparation method

    CN107759079B

  • A high-density tellurite scintillation glass and its preparation method

    CN110451795B

  • Boron-free high-density gadolinium lutetium germanate glass and preparation method thereof

    CN114409252A

  • Gadolinium borosilicate scintillating glass and preparation method thereof

    CN103693847A

  • High-transparency microcrystalline glass containing scintillation nanocrystals and preparation method thereof

    CN112723749A